Evaluation of Menu Nutrition Towards the Nutritional Adequacy of Female Teenage Santri in Pesantren Tahfidz Qur'an Terpadu Al-Hikmah Cirebon - Fitriyani, Dwi Nur; Sholichin, Sholichin (Ann Publisher, 2025)
Pesantren Tahfidz Qur'an Terpadu Al-Hikmah Cirebon is one of the pesantren that implements a self-managed food system that produces 3000 servings of food a day. The study aimed to analyze the level of nutritional adequacy of the meals served—a descriptive observational study using a cross-sectional design. The study population was 516 female students from Junior High School and Madrasah at Al-Hikmah Cirebon Integrated Qur'an Tahfidz Pesantren and the sample was the entire population. Data collection was done through interviews and the food weighing method. The results showed that the average content of energy and macronutrients in the daily food menu served for female students of Pesantren Al-Hikmah Cirebon contained 1923 kcal energy, 51.8 g protein, 61.6 g fat, and 285 g carbohydrates. The nutritional adequacy of female students per day refers to the Nutritional Adequacy Rate according to the Peraturan Menteri Kesehatan Nomor 28 Tahun 2019, namely energy 2075 kcal/hr, protein 65 g / hr, fat 70 g / hr, and carbohydrates 300 g / hr. The results showed that the level of nutritional adequacy of the daily food menu served met 92.6% of energy (less), 79.7% of protein (less), 88.1% of fat (less), and 95% of carbohydrates (less). Deficiencies in nutritional fulfillment can be met from the students' snacks or other foods outside the meal menu served by the pesantren.